Using Geospatial Technologies for Assessing Accessibility of Urban Spaces for People with Motor Disabilities: Theoretical Framework of an Approach Centered on Users’ Perception - Yaagoubi, Reda; Mostafavi, Mir Abolfazl; Edwards, Geoffrey; Noreau, Luc (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2019)
The quality of life of people with disabilities strongly depends on their ability to access urban spaces and conduct their daily activities without any restriction. Unfortunately, there is a significant gap between traditional urban design and the way people with disabilities live in urban environments, which significantly limits their mobility and hence their social participation. In recent years, several governments and administrations have issued norms and guidelines that aim to ensure the construction of environments that are accessible and barrier-free in order to facilitate the mobility of these people. However, the goal and the means to improve mobility and quality of access to urban environments are still misunderstood by the public authorities and the actors involved. In order to help people with disabilities overcome the existing environmental barriers, we need to better understand how they perceive the accessibility of an urban environment while taking into account the heterogeneity of their profiles. In this paper, we present a theoretical framework of a new approach to assess accessibility of urban environments centered on users’ perception. To take into consideration the diversity of users’ profiles, the proposed framework combines the principles of the Disability Creation Process model and ‘Cognitive Design’. These two paradigms provide a solid background for the definition of experimental protocols for assessing the level of accessibility of urban spaces that may contain diverse obstacles and facilitators. In addition, this paper illustrates the importance of geospatial technologies for the implementation of such protocols.